How mothers interact with children with suspected cow's milk allergy symptoms. (18th September 2013) - Merras‐Salmio, Laura; Salo, Saara; Pelkonen, Anna S; Kuitunen, Mikael; Aronen, Eeva T; Mäkelä, Mika J; Kolho, Kaija‐Leena
Abstract Aim To characterize mother–child interaction in children with suspected gastrointestinally manifested cow's milk allergy (GI‐CMA) and to explore factors associated with the parentally perceived symptoms. Methods We invited a randomly selected group of children with suspected GI‐CMA and their mothers to take part in a video recording of them playing together. The mother–child interaction was rated using the Emotional Availability Scales (EAS, 4th edition) and compared with national normative data. Results Video recordings were conducted with 24 patients (15 girls and nine boys) with a median age of 10.1 months (range 2.1–20.5 months) undergoing a double‐blind, placebo‐controlled food challenge for cow's milk allergy. The EAS profile in the challenge negative group (17/24) was significantly different from the normative data. The scores for maternal sensitivity (p = 0.0049) and nonintrusiveness (p = 0.0192), together with child responsiveness (p = 0.0053) and involvement of mother (p = 0.0085), were all significantly lower when compared to the normative data. The dimensions of maternal nonhostility and structuring, as well as the scores of the challenge positive group, did not differ from the normative data. Conclusion Dysfunctional mother–child emotional interaction was frequent in young children with suspected GI‐CMA ruled out by the cow's milk challenge. Appropriate psychological support should be considered.